Factors Associated with Intimate Partner Violence: Logistic Regression Approach - Tiwari, Prativa; Shrestha, Gauri (Nepalese Journal of Statistics, 2018)
Background: Intimate Partner Violence is a major health and human rights problem. Globally, intimate partner violence includes physical act of violence together with sexual coercion, physical threats, psychological abuse and controlling actions by the intimate partner. Objective: This study aims to identify the factors influencing intimate partner violence of married women in Pokhara, Lekhnath Metropolitan City ward number 27, Kaski, Nepal. Materials and Methods: This study is entirely based on the primary data. The sample contains 303 married women of 15-49 years selected by systematic sampling. Data was collected using structured questionnaire and face to face interview. The questionnaire used is modified version of the questionnaire designed and recommended by World Health Organization (WHO) and Program for Appropriate Technology in Health ‘PATH’ (2005). Data was analyzed using descriptive and inferential statistical methods. To determine the significant factors, Logistic regression model was used for establishing linkage between intimate partner violence and several explanatory variables. Results: Fitted model showed the variables, affair with other women and alcohol consumption habit were highly significant predictors for the intimate partner violence. Occupation of husband was significant predictor for physical violence and occupation of respondent was significant for sexual violence. Goodness of fit tests (Hosmer-Lemeshow chi-square statistic, Negelkerke R2) showed that all three models fit well to the proposed Logistic regression model. Conclusion: Although violence is a multidimensional concept, this study has attempted to capture three types of violence namely psychological, physical and sexual called IPV. The IPV was collapsed to create a dichotomous variable on the basis of whether the woman has IPV or not. A number of independent variables are taken into account based on scientific literature review. Nepalese Journal of Statistics, Vol. 2, 37-52